Discovering the Xinyimin in Jakarta: New Chinese Migrants from the prc - Lin, Ping (Translocal Chinese: East Asian Perspectives, 2020)
Abstract The Belt and Road Initiative (bri) has encouraged many prc nationals to move to Indonesia as (informal) entrepreneurs, firm managers, expatriates, petty traders, migrant laborers, or to accompany family members. It is likely that hundreds of thousands of prc nationals have regularly stayed in Indonesia since between 2000 and 2017. This pilot study found that most new Chinese migrants (xinyimin) were middle- or lower-class people from rural areas in the prc. With limited knowledge and capital, it was difficult for them to achieve a stable and affluent life in the major cities of the prc. However, by moving to Jakarta, their limited assets had greater value because of the development gap between Indonesia and the prc. Most such migrants to Indonesia obtain more promising career opportunities, achieve higher socioeconomic status, and enjoy comfortable lives. Those from coastal prc tend to be managers of large firms; those from the inner regions of the country tend to be petty traders, self-employed, labor migrants, or are hired as local staff. The former are more likely to be conservative with respect to Indonesian society and to align themselves with the prc discourse on the bri; the latter are more responsive to Indonesian society. In general, the fewer resources migrants have in the prc, the more likely they are to settle in Indonesia.